ХОЗЯЙСТВЕННАЯ АДАПТАЦИЯ НАСЕЛЕНИЯ ПАЛЕОМЕТАЛЛА НА ПАМЯТНИКЕ КЛЕРК-5 В ПРИМОРЬЕ - ВОСТРЕЦОВ, Юрий Евгеньевич; АРТЕМКИН, Роман Александрович (Гуманитарные исследования в Восточной Сибири и на Дальнем Востоке, 2024)
The article examines the events of the Early Palaeometal epoch, when the multidirectional migration of the farmers from the continental regions of Dongbei to the territory of Primorye took place. At the multi-layered site Klerk 5 in Boysman Bay a habitation horizon left by people about 3,200 years ago was examined. It included a hearth, two units of mollusk shell deposits, pottery, stone tools and a variety of ecofacts. Based on the analysis of the paleogeographical situation, the composition and location of artifacts and ecofacts, the authors reconstruct individual aspects of the life support system and lifestyle of thePaleometal epoch population.